Phosphatidylserine improves axonal transport by inhibition of HDAC and has potential in treatment of neurodegenerative diseases - Shiran Naftelberg; Gil Ast; Eran Perlson (Neural Regeneration Research, 2017)
Familial dysautonomia (FD) is a rare children neurodegenerative disease caused due to a point mutation in the IKBKAP gene that results in decreased IKK complex-associated protein (IKAP) protein production. The disease affects mostly the dorsal root ganglion (DRG) and the sympathetic ganglion. Recently, we found that the molecular mechanisms underlying neurodegeneration in FD patients are defects in axonal transport of nerve growth factors and microtubule stability in the DRG. Neurons are highly polarized cells with very long axons. In order to survive and maintain proper function, neurons depend on transport of proteins and other cellular components from the neuronal body along the axons. We further demonstrated that IKAP is necessary for axon maintenance and showed that phosphatidylserine acts as an HDAC6 inhibitor to rescue neuronal function in FD cells. In this review, we will highlight our latest research findings.